Environmental Pollution and Public Health Implications of Poor Solid Waste Management Practices in Developing Countries: Evidence from Urban Cities in Nigeria - Kehinde Emmanuel Agbeni; Hadiza Nuhu Ajoge; Ewurum Chukwuemeka Promise; Sunday bakel Samuel; Ogegere Ogheneochukome Evelyn; Ogegere Oghenemudiakevwe Franklyn; Kazeem Ojuade; Bernice Asamoah Boahene (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2025)
Purpose - This study investigates the health and environmental impacts of poor solid waste management practices in urban cities across Nigeria. It explores how increasing population and urbanization contribute to rising waste volumes and the reliance on open dumpsites, which pose serious risks to public health and the environment. Design/methodology/approach - A mixed-methods research design was adopted, combining survey questionnaires and in-depth interviews. Field data were collected from three urban areas where open dumping is common. A total of 150 questionnaires were distributed to residents living within a two-kilometer radius of the dumpsites, with 138 valid responses received (92% response rate). In addition, ten interviews were conducted with waste management officials and healthcare personnel. Data were analyzed using descriptive statistics. Originality -  This study contributes to the understanding of the link between improper waste disposal and public health in the Nigerian urban context. It highlights the socio-environmental consequences of unmanaged waste and offers insights into the institutional and community-level responses. Findings and Discussion - The results reveal that existing waste management systems in Nigerian urban centers are largely ineffective. Poor waste handling practices have led to increased cases of communicable diseases such as malaria, cholera, typhoid, and diarrhea. However, the study also identifies economic opportunities in recycling and waste-related employment, if properly managed. Conclusion - The findings underscore the need for stronger public awareness, improved waste recycling infrastructure, and strict enforcement of environmental laws. A sustainable waste management strategy should combine community education with institutional reforms to reduce health risks and improve environmental quality.